Property and Business Valuation Law – Procedures Organization Priority and Unrevealed Aspects of Valuers’ Practice and Methodology (Parliamentary Studies, 2012)
Property and business valuers’ profession and property and business valuation history in Lithuania stretches for almost twenty years. Legal regulation acts of this sphere have a 15 year or a bit longer history, which changed and developed together with valuation services.Targeted regulation influences and will continue to influence property valuation practices, profession’s prestige and image in the market society.The aim of this article is to overview the legal regulation principles of Lithuania’s property valuers’ professional practices and their transformation while forming valuers’ professional readiness and maturity. Legislative provisions are analyzed in order to summarize the existing publications and researches, provide insights for the future.
Keywords: valuers’ profession; valuation service; continuous regulation of property and business valuation